Components of Kurdish Folk Song in Erbil - Karwan Othman Taha; Nasr hashm badan; Rizgar mohamad shikh mohamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
This research attempts to analyze the content and main (components of the Kurdish folk song in Erbil) in terms of melody, poetry, rhythm and form, which are the basis and source of the song. Not only conducting a scientific analysis on the main principles of Kurdish folk songs in general and Erbil folklore in particular will help archiving these songs and preserving them from extinction, but also very important for preserving Kurdish song culture and providing notes for these songs Art academies in Kurdistan and enriching Kurdish libraries with artistic resources. The researcher analyzed several Kurdish folk songs in Erbil as examples of the research to present the songs' main components.